2021
DOI: 10.1016/j.critrevonc.2020.103127
|View full text |Cite
|
Sign up to set email alerts
|

Multikinase inhibitor-induced liver injury in patients with cancer: A review for clinicians

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 253 publications
(182 reference statements)
0
8
0
Order By: Relevance
“…Houron et al have published a comprehensive literature review on multikinase inhibitor‐related hepatotoxicity. The authors reported that the latency is usually between one week to two months, and the TKI‐related liver toxicity is often hepatocellular and less frequently mixed 9 . When it comes to osimertinib, the latency is 15 days to one month 3–5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Houron et al have published a comprehensive literature review on multikinase inhibitor‐related hepatotoxicity. The authors reported that the latency is usually between one week to two months, and the TKI‐related liver toxicity is often hepatocellular and less frequently mixed 9 . When it comes to osimertinib, the latency is 15 days to one month 3–5 .…”
Section: Discussionmentioning
confidence: 99%
“…The DILI network categorizes liver injury into 18 histological patterns 10–12 . Previous reports of liver biopsy pathology of EGFR TKI (gefitinib, erlotinib) showed active hepatitis with portal inflammation and bridging fibrosis 9 . In the case reported by Gonzalez et al, the pathology of liver biopsy revealed pericentral confluent necrosis which is classified as zone necrosis in the DILI network system and the portal tracts showed mild nonspecific chronic inflammation 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al [99] Rate of ILICI in combination therapy of an anti-CTLA-4 and anti-PD-1 (9.2%) compared with monotherapy with an anti-CTLA-4 (1.7%) or anti-PD-1 (1.1%) multi-kinase inhibitors used in clinical practice [128]. They noted that any aminotransferase elevation was exceedingly common, and that grade 3-4 hepatitis, defined as aminotransferase levels > 5× ULN, has been detected in 0-29% of patients treated with tyrosine kinase inhibitors in clinical trials.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…The authors note that while most cases are asymptomatic and reversible, there is a 0.2-0.5% prevalence of acute liver failure related to afatinib, ceritinib, crizotinib, and regorafenib. Therefore, they recommend routine laboratory monitoring of ALT during treatment with tyrosine kinase inhibitors [128]. Liver test monitoring as part of a Risk Evaluation and Mitigation Strategy has been recommended for pexidartinib, a newly approved colony-stimulating factor-1 receptor inhibitor used in the management of patients with tenosynovial giant cell tumors [129].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%